First record of the blacktip reef shark Carcharhinus melanopterus (Carcharhiniformes: Carcharhinidae) from the Tropical Eastern Pacific - López-Garro, Andrés (Universidad de Costa Rica, 2012)
El tiburón punta negra de arrecife, Carcharhinus melanopterus, es uno de los tiburones de arrecife más comunes del Indo-Pacífico. Durante una expedición cientí- fica al Parque Nacional Isla del Coco, Costa Rica, Pacífico Tropical Oriental, un tiburón punta negra de arrecife fue capturado en Bahía Chatham, Parque Nacional Isla del Fig. 2. Carcharhinus melanopterus captured at Chatham Bay, Isla del Coco National Park. A) Detailed is the short and rounded snout with large anterior nasal flaps. B) Image shows prominent first dorsal fin with black tip and a light band below it. C) Image shows the black edge of the upper lobe of the caudal fin. D) Body coloration of the blacktip reef shark from Chatham Bay, Isla del Coco National Park: yellow-brown on the dorsal surface and white on the ventral region, with a dark band on its flanks. Photos A-C: Carlos Hiller. Coco, el 29 de abril 2012. El espécimen capturado era un macho juvenil de 89 cm. Este es el primer informe de esta especie para el Parque Nacional Isla del Coco, Costa Rica y para el Pacífico Tropical Oriental.